2020
DOI: 10.2196/18813
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Dimensions of Medical Crowdfunding: A Visual Analytics Approach

Abstract: Background Medical crowdfunding has emerged as a growing field for fundraising opportunities. Some environmental trends have driven the emergence of campaigns to raise funds for medical care. These trends include lack of medical insurance, economic backlash following the 2008 financial collapse, and shortcomings of health care regulations. Objective Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 64 publications
4
39
0
Order By: Relevance
“…Since social media can reach varied stakeholders and a wide audience in society, nongovernmental health organizations can use social media to mobilize social resources. Studies found that these organizations leveraged social media to advocate for change in public policies related to health issues such as HIV/AIDS [62] and mental health [63], raise funds for individual medical care and health-related research [64,65], and raise awareness and promote actions to address health problems such as medical equipment shortages [66]. Although a formal test of the effectiveness of using social media for social mobilization is lacking, the successful cases described in the articles show that social media provides a platform for nongovernmental health organizations to effectively mobilize resources and advocate for collective actions to achieve their goals [62].…”
Section: Social Mobilizationmentioning
confidence: 99%
“…Since social media can reach varied stakeholders and a wide audience in society, nongovernmental health organizations can use social media to mobilize social resources. Studies found that these organizations leveraged social media to advocate for change in public policies related to health issues such as HIV/AIDS [62] and mental health [63], raise funds for individual medical care and health-related research [64,65], and raise awareness and promote actions to address health problems such as medical equipment shortages [66]. Although a formal test of the effectiveness of using social media for social mobilization is lacking, the successful cases described in the articles show that social media provides a platform for nongovernmental health organizations to effectively mobilize resources and advocate for collective actions to achieve their goals [62].…”
Section: Social Mobilizationmentioning
confidence: 99%
“…Xu and Wang (2019) and Ba et al (2021) extend the research to the context of China. Regarding the role of social media in MC, Beier and Wagner (2015), Lu et al (2015), and Ren et al (2020) show that social media helps to spread MC campaigns. Berliner and Kenworthy (2017) and Kubheka (2020) emphasize the requirement of digital skills in MC successful in social media.…”
Section: Introductionmentioning
confidence: 99%
“…There are three ways to access medical campaigns through the US version of the GoFundMe website: accessing a list of 1,000 campaigns selected algorithmically by the site, listed in the 'Medical' category of the 'Discover' page; searching for campaigns with a specific keyword (e.g., 'cancer'); or obtaining a direct link to a campaign through social media or similar means. Like other recent research on GoFundMe (Ren et al, 2020;Saleh et al, 2020), we used the first approach, since it is in practice the most viable means of obtaining a wide variety of campaigns across the US that are guaranteed to be in the medical category. The most viable alternative would be to use the search feature, but that would limit results to campaigns that match pre-defined keywords.…”
Section: Methodsmentioning
confidence: 99%